ANALISIS BIBLIOMETRIK PERKEMBANGAN PENELITIAN HABITAT ANOA - Heru Z Thalib; Dewi Wahyuni K Baderan; Marini Susanti Hamidun; Sukirman Rahim; Iswan Dunggio; Daud Yusuf (Jurnal Bionatural, 2024)
This study investigates the evolution of research trends concerning the conservation of anoa habitats. It aims to track the growth in the number of national and international publications indexed by Google Scholar that focus on anoa. The data was collected using the keywords “anoa” AND “Conservation” for the period 2014 - 2024. The analysis was conducted using Publish or Perish and VOSViewer. The findings reveal that 856 articles were published between 2014 and 2024. The annual distribution is as follows: 51 articles in 2014 (5.96%), 41 in 2015 (4.78%), 70 in 2016 (8.18%), 90 in 2017 (10.51%), 78 in 2018 (9.11%), 97 in 2019 (11.33%), 96 in 2020 (11.21%), 93 in 2021 (10.86%), 114 in 2022 (13.32%), 103 in 2023 (12.03%), and 23 articles up to March 2024 (2.69%), totaling the publications over the past decade. The research linkage mapping on anoa yielded four clusters: Cluster 1 contains 7 keywords, Cluster 2 comprises 6 keywords, Cluster 3 includes 3 keywords, and Cluster 4 features 2 keywords.